Analisis Pengaruh Gaya Kepemimpinan Terhadap Komitmen Organisasi di Sekolah Tinggi Agama Islam (STAI) Provinsi Riau - Masriani Masriani; Syarifudin Syarifudin; Moh. Sain; Hasnawati Hasnawati; Mardiah Mardiah; Faridatul Faridatul; Bashori Bashori (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The purpose of this study was to determine the effect of leadership style on organizational commitment at the Islamic College (STAI) in Riau Province. This research is a quantitative study with a survey method approach. The results of this study indicate that the leadership style of the head of the Islamic College of Religion (STAI) in Riau Province has a significant effect on institutional organizational commitment. This is shown through the calculation results, namely; the value of tcount (9.198)> ttable (1.969), so that H0 is rejected and H1 is accepted. This means that the application of a good leadership style (positive) will greatly affect the increase in organizational commitment. Therefore, the implication of this study is that the right leadership style will affect organizational commitment in the Islamic Religious College of Riau Province.